Incidencia de la lectura crítica en el rendimiento académico de los estudiantes de tercero y cuarto año de educación básica de la escuela fiscal mixta “Teófilo Segovia” del recinto Puembo, parroquia El Tingo, cantón Pujilí, periodo lectivo 2012-2013 - Almachi Coro, Tatiana Clarivel (2014)
The present study aimed to determine the incidence of critical reading in the academic performance of students in third and fourth year of basic education of the Joint Fiscal school " Teofilo Segovia " Puembo Campus. The proposed topic is considered sustainable development and sustainable academic considering that at the present time requires a quality education and warmth bound for education excellence. This research sought to establish by analyzing the development of a module, and also give a workshop for teachers about the techniques and strategies of critical reading, in order to achieve spontaneous participation and improve performance in students taking that the problems in school performance by inefficient application of methodological strategies, lack of motivation and socioeconomic environment are given.